DAMPAK DISIPLIN PADA KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL PERANTARA - Tobing, Han Martine; Siahaan, Rumiris; Rajagukguk, Rudi (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2022)
The aim of this research is to analyze the effect of discipline on employee performance mediated by motivational variables. The research method uses quantitative types, with the help of SPSS Version 25.00. Data was collected from distributing questionnaires to employees of the food and agriculture security service in the city of Tebing Tinggi. as many as 50 people. The method of analysis uses an instrument test, namely the validity of the data and reliability. The classic assumptions are norm, multicollinearity, heteroscedasticity, multiple linear regression analysis, coefficient of determination. The hypothesis was tested using the t test and path analysis. Research results: Discipline (X1) affects motivation (Z) Work discipline (X1) influences performance (Y), motivation (Z) influences performance (Y) The direct effect of work discipline (X1) on performance (Y) is 0.352 while indirect effect through the variable motivation (Z), namely 0.500 x 0.398 = 0.199. This means that the indirect effect through motivation (Z) is smaller than the direct effect on performance (Y), the fourth hypothesis is rejected. Motivation has no criteria as a mediating variable.